Integer Representation of Floating-Point Manipulation with Float Twice - Wakhid Kurniawan; Hafizd Ardiansyah; Annisa Dwi Oktavianita; Mr. Fitree Tahe (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
In the programming world, understanding floating point is not easy, especially if there are floating point and bit-level interactions. Although there are currently many libraries to simplify the computation process, still many programmers today who do not really understand how the floating point manipulation process. Therefore, this paper aims to provide insight into how to manipulate IEEE-754 32-bit floating point with different representation of results, which are integers and code rules of float twice. The method used is a literature review, adopting a float-twice prototype using C programming. The results of this study are applications that can be used to represent integers of floating-point manipulation by adopting a float-twice prototype. Using the application programmers make it easy for programmers to determine the type of program data to be developed, especially those running on 32 bits floating point (Single Precision).